2015
DOI: 10.3390/molecules201119657
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Effects of Artemisia scoparia Waldst in Spontaneously Hypertensive Rats and Identification of Angiotensin I Converting Enzyme Inhibitors

Abstract: Abstract:We investigated the antihypertensive effects of Artemisia scoparia (AS) in spontaneously hypertensive rats (SHR). The rats were fed diets containing 2% (w/w) hot water extracts of AS aerial parts for 6 weeks. The AS group had significantly lower systolic and diastolic blood pressure levels than the control group. The AS group also had lower angiotensin I converting enzyme (ACE) activity and angiotensin II content in serum compared to the control group. The AS group showed higher vascular endothelial g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…In addition, sesquiterpene lactones and scopoletins have been reported to show antioxidative and anti-inflammatory activities (27)(28)(29)(30)(31). We previously found that the aerial part of A. scoporia reduced plasma lipid peroxidation and protein carbonyl oxidation and suppressed tumor necrosis factor alpha and NF-κB expression induced in spontaneously hypertensive rats (14). Therefore, the sesquiterpene lactones and scopoletins identified in this study might be partially responsible for the antioxidant and anti-inflammatory activities of A. scoparia.…”
Section: Ace Inhibitory Activity Of Isolated Compoundsmentioning
confidence: 50%
See 3 more Smart Citations
“…In addition, sesquiterpene lactones and scopoletins have been reported to show antioxidative and anti-inflammatory activities (27)(28)(29)(30)(31). We previously found that the aerial part of A. scoporia reduced plasma lipid peroxidation and protein carbonyl oxidation and suppressed tumor necrosis factor alpha and NF-κB expression induced in spontaneously hypertensive rats (14). Therefore, the sesquiterpene lactones and scopoletins identified in this study might be partially responsible for the antioxidant and anti-inflammatory activities of A. scoparia.…”
Section: Ace Inhibitory Activity Of Isolated Compoundsmentioning
confidence: 50%
“…Interestingly, compounds 3 and 4, which possess dihydroxyl and epoxy groups at the C-3 and C-4 positions, respectively, showed significantly higher ACE inhibitory activities than other sesquiterpene lactones (1, 2, 5, and 6), and their activities were similar to that of quercetin. Isofraxidin 7-O-β-Dglucopyranoside, a glucoside of isofraxidin (9) identified in this study, has been reported to show ACE inhibitory activity (14,26). In addition, sesquiterpene lactones and scopoletins have been reported to show antioxidative and anti-inflammatory activities (27)(28)(29)(30)(31).…”
Section: Ace Inhibitory Activity Of Isolated Compoundsmentioning
confidence: 55%
See 2 more Smart Citations
“…Cho and co-workers, in two separate studies on Artemisia scoparia, demonstrated the effectiveness of purified IF (1 mM) on the blockade of ACE activity (69.0%). Also IF isolated during the EtOAc and chloroform extraction of aerial parts of Artemisia scoparia, showed ACE inhibitory effects at 26.1% and 30.6%, respectively [59,136]. On the other hand, Simaratanamongkol and co-workers demonstrated the synergistic effects of IF isolated from Apium graveolens, with junipediol A on the inhibition of ACE.…”
Section: Cardioprotective Effectsmentioning
confidence: 99%